Dampak Pandemi Covid-19 Terhadap Minat Belajar Matematika Mahasiswa - Nurdiana Siregar; Nurkhairunnisa Siregar (STKIP Andi Matappa Pangkep, 2021)
This study aims to see the impact of the Covid-19 pandemic on students' interest in learning mathematics while studying online. This research is included in qualitative research with descriptive method in which the research uses survey techniques with a questionnaire instrument of interest in learning mathematics to collect data on student interest. The data analysis technique used in this research is the flow model which consists of reducing data, presenting data, and drawing conclusions. The results of the study showed that as many as 49.99% of students of the PGMI study program had an interest in learning mathematics in online learning during the Covid-19 pandemic in low grade MI/SD mathematics studies courses. This means that 50.01% of PGMI study program students have no interest in learning mathematics online.